Gender and governance in rural services: Insights from India, Ghana, and Ethiopia - Asante, Felix; Banful, Afua B.; Birner, Regina; Cohen, Marc J.; Gaff, Peter; Gayathridevi, K. G.; Horowitz, Leah; Lemma, Mamusha; Mogues, Tewodaj; Palaniswamy, Nethra; Paulos, Zelekawork; Raabe, Katharina; et al. (World Bank, 2010)
As the first output from the gender and governance in rural services project, this report presents descriptive findings and qualitative analysis of accountability mechanisms in agricultural extension and rural water supply in India, Ghana, and Ethiopia, paying specific attention to gender responsiveness. The gender and governance in rural services project seeks to generate policy-relevant knowledge on strategies to improve agricultural and rural service delivery, with a focus on providing more equitable access to these services, especially for women. The project focuses on agricultural extension, as an example of an agricultural service, and drinking water, as an example of rural service that is not directly related to agriculture but is of high relevance for rural women. A main goal of this project was to generate empirical micro level evidence about the ways various accountability mechanisms for agricultural and rural service provision work in practice and to identify factors that influence the suitability of different governance reform strategies that aim to make service provision more gender responsive. Three out of four poor people in the developing world live in rural areas, and most of them depend directly or indirectly on agriculture for their livelihoods. Providing economic services, such as agricultural extension, is essential to using agriculture for development. At the same time, the rural poor need a range of basic services, such as drinking water, education, and health services. Such services are difficult to provide in rural areas because they are subject to the "triple challenge" of market, state, and community failure. As a result of market failure, the private sector does not provide these services to the rural poor to the extent that is desirable from society's point of view. The state is not very effective in providing these services either, because these services have to be provided every day throughout the country, even in remote areas, and because they require discretion and cannot easily be standardized, especially if they are demand driven. Nongovernmental organizations (NGOs) and communities themselves are interesting alternative providers of these services, but they too can fail, because of capacity constraints and local elite capture. This triple challenge of market, state, and community failure results in the poor provision of agricultural and rural services, a major obstacle to agricultural and rural development.